The circular model of “SOME” on digital public relations management of Universitas Islam Riau - Qurniawati, Eka Fitri; Mardani, Puri Bestari; Wulandari, Happy (PRofesi Humas, 2024)
Background: The transition of information channels used by the general public today is increasingly centered on digital media. This is indeed an opportunity for various institutions to enter the target market without having to go through filters as before. So, by reading this pattern Universitas Islam Riau adapts its public relations strategy from conventional to digital wisely. Purpose: This research was conducted to explore how UIR used digital in its public relations strategy. Methods: To understand the situation and the data collected, this research uses the SOME (share, optimize, manage, engage) model in elaboration. As for the research, the descriptive qualitative method is chosen as an approach to understanding five informants who were on the public relations team for UIR. Results: Following the SOME model, it can be mapped that in share, UIR used five social media and a website. Optimize, by arranging social media surfaces and collaborating with public figures. In managing, they monitor every audience response to each post through social media insight features, as well as direct and real-time actions to the audience on social media accounts. In engage, to publish the latest information and respond to all incoming messages. Conclusion: UIR uses digital public relations in managing information, going through four main stages, starting from the process of sharing, optimizing, managing, and attracting. Implications: The results of this study can provide input to university public relations to manage digital public relations optimally to always increase and build audience trust effectively and quickly.